The Investigation of the Accessibility of Children's Playgrounds in the Town of Ordu - Murat Yeşil; Pervin Yeşil (Turkish Journal of Agriculture: Food Science and Technology)
Children's playgrounds which are safe and quiet environments that children can play there have started to become rare as a result of rapid urbanization. Because, the studies have shown that unplanned and distorted urban spaces affect children's behaviours, attitudes and reactions in a bad way. In this study, the availability of children's playgrounds in 22 districts of the city centre of Ordu was investigated. In this context, firstly, children's play areas were determined based on the neighbourhood scale and then area calculations were made and the amount of play area by per child between 0-14 years was calculated in each district. In the second stage, accessibility maps for children's playgrounds were obtained by determining the availability of the playgrounds at 200m distance. The results of this study showed that children's playgrounds are not balanced in the city, increased in some districts, in some cases they are not within reachability limits and can not meet their needs.